2022
DOI: 10.3390/psychoactives1010003
|View full text |Cite
|
Sign up to set email alerts
|

Tripping to Cope: Coping Strategies and Use of Hallucinogens during the COVID-19 Pandemic in Three Cultural Contexts

Abstract: The COVID-19 pandemic has made evident the need to develop effective strategies to cushion the psychological consequences of social catastrophes. Preliminary evidence suggests that the use of hallucinogens is a protective factor that mitigates against such stressors. However, the underlying mechanisms must be further explored. This study specifically focused on the potential role of coping strategies in this regard, analyzing them through an online survey completed by a total of 2971 subjects who were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 87 publications
(110 reference statements)
1
6
0
Order By: Relevance
“…The yAPD group demonstrated higher problem-focused coping scores, compared to the nAPD group, albeit emotion-focused coping did not differ between the two groups. These results are aligned with a previous study demonstrating that hallucinogen usage led to increased problem-focused, but not emotional coping engagement when dealing with the challenges posed by COVID-19 ( 77 ). Generally, problem-focused coping involves taking practical steps toward actively addressing the source of stress or problem, while emotion-focused coping focuses on managing and regulating emotions in response to stress without directly addressing the stressor itself ( 107 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The yAPD group demonstrated higher problem-focused coping scores, compared to the nAPD group, albeit emotion-focused coping did not differ between the two groups. These results are aligned with a previous study demonstrating that hallucinogen usage led to increased problem-focused, but not emotional coping engagement when dealing with the challenges posed by COVID-19 ( 77 ). Generally, problem-focused coping involves taking practical steps toward actively addressing the source of stress or problem, while emotion-focused coping focuses on managing and regulating emotions in response to stress without directly addressing the stressor itself ( 107 ).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies provided evidence of enhanced coping abilities among psychedelic users ( 17 , 77 , 104 , 105 ), and the modulatory role of 5-HT1A and 5-HT2A receptors in shaping coping styles has been suggested ( 106 ). However, the particular experiential aspects that serve as mechanisms of change have received minimal investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, regular use of hallucinogenic drugs was specifically associated with higher scores on the PTG scales (relating to others, new possibilities, personal strength, spiritual change, and appreciation of life). In relation to that, another manuscript focused on coping strategies and use of hallucinogens showed that regular users of these drugs are more prone to use adaptive coping strategies 62 . This is highly relevant in the context of the recently published research on the potential of MDMA for the treatment of PTSD 63 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, therefore, that the willingness that users tend to show toward exposing themselves to highly challenging experiences is somehow related to their better PTG scores. In addition, this continuous exposure to challenging experiences could have provided personal resources to deal with pandemic stress, partially explaining the better scores on mental health and well-being they showed in different studies 34 , 62 . Previous research has shown different personality traits between hallucinogenic drug users and non-users, especially in the case of ayahuasca, as well as differences between users depending on the environment in which they live 31 , 76 .…”
Section: Discussionmentioning
confidence: 99%